Promoting Gender Equality for Accountants Religiously: A Collaborative Approach - Prasetyo, Ismarh Fadhlillah; Sawarjuwono, Tjiptohadi (The Indonesian Accounting Review, 2023)
Gender inequality remains a concerning issue in accounting professions, primarily due to the prevalence of traditional masculine values. Additionally, religious perspectives often assign women the roles of mothers and wives within households. However, it is important to note that Allah views men and women as equals in this world, differentiating them only through faith and piety. Considering this standpoint, this study employs a religious approach to address and diminish the influence of masculinity values and promote gender equality within Islamic principles. To achieve this, the study identifies and examines the masculinity values that perpetuate gender inequality within the accounting profession, using documentary research methods. The investigation reveals several masculinity values that justify gender disparities in this field. To counteract these harmful values, the study draws a parallel between leadership and accounting and proposes relevant Islamic values that can challenge and neutralize the identified masculinity norms, thereby fostering gender equality. This research contributes to the refinement of the religious approach by acknowledging and addressing the influence of masculinity values that contribute to gender inequality and replacing them with Islamic values that promote fairness and equity.